2022
DOI: 10.1371/journal.pone.0267140
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of nasal microbiota and clinical parameters in a multi-parametric prediction model to differentiate bacterial versus viral infections in lower respiratory tract infections

Abstract: Background The ability to accurately distinguish bacterial from viral infection would help clinicians better target antimicrobial therapy during suspected lower respiratory tract infections (LRTI). Although technological developments make it feasible to rapidly generate patient-specific microbiota profiles, evidence is required to show the clinical value of using microbiota data for infection diagnosis. In this study, we investigated whether adding nasal cavity microbiota profiles to readily available clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Ramgopal et al derived an ML model to predict serious bacterial infections in young febrile infants [ 65 ]. Lien et al [ 66 ] have recently shown that an ML model using only complete blood count with differential leukocyte count data achieved similar performance as procalcitonin data in bacteremia prediction and Li et al [ 67 ], showed in 293 patients with suspected lower respiratory tract infections and/or sepsis that the most predictive variable was CRP. New experimental methods for viral/bacterial classification also build on ML methods; a nice example is the use of ML on infrared spectroscopy to diagnose inaccessible infections [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ramgopal et al derived an ML model to predict serious bacterial infections in young febrile infants [ 65 ]. Lien et al [ 66 ] have recently shown that an ML model using only complete blood count with differential leukocyte count data achieved similar performance as procalcitonin data in bacteremia prediction and Li et al [ 67 ], showed in 293 patients with suspected lower respiratory tract infections and/or sepsis that the most predictive variable was CRP. New experimental methods for viral/bacterial classification also build on ML methods; a nice example is the use of ML on infrared spectroscopy to diagnose inaccessible infections [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the host PAB machinery alone provides factors that may influence trends in COVID-19 vulnerability and resistance, it is important to recall that human genetics are only one determinant of our pathophysiologically relevant proteome. A crucial component of human biochemical complexity and diversity emerges from microbial complementarity, with distinct microbiomes in upper respiratory [159][160][161][162][163], lower respiratory [115,[164][165][166][167], and gastrointestinal tracts [166][167][168][169][170] all having tangibly different effects on viral outcomes. Among the various biochemical effects associated with microbial proteases are known modulations of the innate immune system including IFNγ, several interleukins, and others [171], plus proteolytic stabilization of viral capsids in a manner that may bolster virion persistence outside of hosts in moist environments [172].…”
Section: Microbiotic Mimicry and Amplification Of Protease/antiprotea...mentioning
confidence: 99%